Mesoporous Silica and Oligo (Ethylene Glycol) Methacrylates-Based Dual-Responsive Hybrid Nanogels - Macchione, Micaela Alejandra (2022)
Polymeric-inorganic hybrid nanomaterials have emerged as novel multifunctional platforms because they combine the intrinsic characteristics of both materials with unexpected properties that arise from synergistic effects. In this work, hybrid nanogels based on mesoporous silica nanoparticles, oligo (ethylene glycol) methacrylates, and acidic moieties were developed employing ultrasound-assisted free radical precipitation/dispersion polymerization. Chemical structure was characterized by infrared spectroscopy and nuclear magnetic resonance. Hydrodynamic diameters at different temperatures were determined by dynamic light scattering, and cloud point temperatures were determined by turbidimetry. Cell viability in fibroblast (NIH 3T3) and human prostate cancer (LNCaP) cell lines were studied by a standard colorimetric assay. The synthetic approach allows covalent bonding between the organic and inorganic components. The composition of the polymeric structure of hybrid nanogels was optimized to incorporate high percentages of acidic co-monomer, maintaining homogeneous nanosized distribution, achieving appropriate volume phase transition temperature values for biomedical applications, and remarkable pH response. The cytotoxicity assays show that cell viability was above 80% even at the highest nanogel concentration. Finally, we demonstrated the successful cell inhibition when they were treated with camptothecin-loaded hybrid nanogels.